The identity of Stemodia lanceolata (Plantaginaceae) and its occurrence in Brazil - Scatigna, André Vito; Sosa, Maria De Las Mercedes; Souza, Vinicius Castro; Simões, André Olmos (Phytotaxa, 2018)
In this contribution, we reassess the identity of Stemodia lanceolata (Plantaginaceae) and confirm its occurrence in Brazilian territory. We present a detailed and updated description, a fine illustration, and photographs of this species, along with comments on its distribution, habitat and phenology, and notes on taxonomic affinities. Stemodia lanceolata is characterized by its stiffy erect terminal inflorescence with filamentous aspect due to the long, linear-triangular, frequently out-curved floral bracts. Finally, we propose second-step lectotypifications for three names subordinated to S. lanceolata.